2020
DOI: 10.1186/s12886-020-01639-y
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy combined with penetrating keratoplasty and transscleral-sutured intraocular lens implantation in complex eyes: a case series

Abstract: Background The aim of this study was to evaluate the clinical outcomes of pars plana vitrectomy (PPV) combined with penetrating keratoplasty (PKP) and transscleral-sutured intraocular lens (IOL) implantation (IOL-suture) in complex eyes. Methods In this prospective, consecutive interventional case series, patients who underwent PKP combined with PPV and IOL implantation from July 2014 to March 2018 at Yokohama Minami Kyosai Hospital were enrolled. The postoperative best corrected visual acuity (BCVA) (conver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Some studies prove penetrating keratoplasty combined with vitrectomy to be a safe and effective procedure [ 21 , 22 , 23 , 24 , 25 ]. However, another study showed poorer outcomes in patients with severe ocular trauma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies prove penetrating keratoplasty combined with vitrectomy to be a safe and effective procedure [ 21 , 22 , 23 , 24 , 25 ]. However, another study showed poorer outcomes in patients with severe ocular trauma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%